Happiness in US military veterans: Results from a nationally representative study. - Hun Kang; Ian C Fischer; Peter J Na; Robert H Pietrzak (PLoS ONE)
In line with the US Department of Veterans Affairs' adoption of a Whole Health approach to healthcare, there has been growing interest in factors linked to veterans' perceptions of well-being. To date, no known study has examined levels and correlates of perceived happiness in this population. To examine this question, we analyzed data from the National Health and Resilience in Veterans Study, which surveyed a nationally representative sample of 4,069 US military veterans. Overall, veterans reported mean happiness scores of 5.41 out of 7. Greater purpose in life was the strongest correlate of happiness, followed by lower severity of depressive symptoms, and higher optimism, emotional stability, and resilience. Among veterans who screened positive for depression, those who scored higher on measures of optimism, emotional stability, and resilience reported greater happiness. Interventions to leverage these modifiable psychosocial characteristics may help promote happiness and subjective well-being in this population.